Geographical Distribution of Genetic Variants and Lineages of SARS-CoV-2 in Chile - Castillo, Andrés E.; Parra, Bárbara; Tapia, Paz; Lagos, Jaime; Arata, Loredana; Acevedo, Alejandra; Andrade, Winston; Leal, Gabriel; Tambley, Carolina; Bustos, Patricia; Fasce, Rodrigo; Fernández, Jorge (Frontiers in Public Health, 2020)
The pandemic caused by the new coronavirus SARS-CoV-2 is a worldwide public health concern. First confined in China, and then disseminated widely across Europe and America, has impacted and moved the scientific community around the world to working in a fast and coordinated way to collect all possible information about this virus and generate new strategies and protocols to try to stop the infection. During March 2020, more than 16,000 full viral genomes have been shared in public databases, that allow construction of genetic landscapes for tracking and monitoring the viral advances over time and study the genomic variations present in geographic regions. In this work we present the occurrence of genetics variants and lineages of SARS-CoV-2 in Chile during March to April 2020. Complete genome analysis of 141 viral samples from different regions of Chile, revealed a predominance of variant D614G like in Europe and USA and the majority presence of lineage B.1. These findings could help take control measures due to the similarity of the viral variants present in Chile, compared with other countries, and monitor the dynamic change of virus variants in the country.